The Case for Copyright: Protecting Originality and the Architect’s Rights of Ownership - (:unkn) unknown (My University, 1998)
The Architectural Works Copyright Protection Act of 1990 provides valuable protection for architects in a specific condition: It prevents their designs and drawings from being reused without their permission or compensation. Nonetheless, it has raised some interesting questions as to the definition of “architectural works,” what actually merits copyright protection and what constitutes real originality.